Substrate Elasticity Exerts Functional Effects on Primary Microglia - Blaschke, Stefan J.; Demir, Seda; König, Anna; Abraham, Jella-Andrea; Vay, Sabine U.; Rabenstein, Monika; Olschewski, Daniel N.; Hoffmann, Christina; Hoffmann, Marco; Hersch, Nils; Merkel, Rudolf; Hoffmann, Bernd; et al. (Frontiers in Cellular Neuroscience, 2020)
Microglia - the brain’s primary immune cells - exert a tightly regulated cascade of pro- and anti-inflammatory effects upon brain pathology, either promoting regeneration or neurodegeneration. Therefore, harnessing microglia emerges as a potential therapeutic concept in neurological research. Recent studies suggest that - besides being affected by chemokines and cytokines - various cell entities in the brain relevantly respond to the mechanical properties of their microenvironment. For example, we lately reported considerable effects of elasticity on neural stem cells, regarding quiescence and differentiation potential. However, the effects of elasticity on microglia remain to be explored. Under the hypothesis that the elasticity of the microenvironment affects key characteristics and functions of microglia, we established an in vitro model of primary rat microglia grown in a polydimethylsiloxane (PDMS) elastomer-based cell culture system. This way, we simulated the brain’s physiological elasticity range and compared it to supraphysiological stiffer PDMS controls. We assessed functional parameters of microglia under "resting" conditions, as well as when polarized towards a pro-inflammatory phenotype (M1) by lipopolysaccharide (LPS), or an anti-inflammatory phenotype (M2) by interleukin-4 (IL-4). Microglia viability was unimpaired on soft substrates, but we found various significant effects with a more than two-fold increase in microglia proliferation on soft substrate elasticities mimicking the brain (relative to PDMS controls). Furthermore, soft substrates promoted the expression of the activation marker vimentin in microglia. Moreover, the M2-marker CD206 was upregulated in parallel to an increase in the secretion of Insulin-Like Growth Factor 1‎ (IGF-1). Upregulation of CD206 was abolished by blockage of stretch-dependent chloride channels. Our data suggest that cultivation of microglia on substrates of brain-like elasticity promotes a basic anti-inflammatory activation state via stretch-dependent chloride channels. The results highlight the significance of the omnipresent but mostly overlooked mechanobiological effects exerted on microglia and contribute to a better understanding of the complex spatial and temporal interactions between microglia, neural stem cells, and glia, in health and disease.